Corporate Liability for Creditors’ Losses during the Covid-19 Pandemic - Johan, Suwinto; Ariawan, Ariawan (Fakultas Hukum Universitas Muhammadiyah Yogyakarta, 2021)
Many companies experienced bankruptcy lawsuits during the Covid-19 pandemic in 2020. This was so when the companies’ asset cannot afford their obligations upon their creditors, especially banks and other financial institutions. The creditors demanded compensation to avoid losses due to the companies’ failure in repaying their loans. The question is who should be held liable if the companies are of limited liability companies. This paper aims to examine the liability of corporation for creditors' losses. This normative legal research relies on secondary data in the form of legal materials, especially primary and secondary legal materials. The result shows that demanding compensation through bankruptcy lawsuit is not an easy task for the creditors. In fact, a separate lawsuit is required rather than incorporating it in a bankruptcy lawsuit. Even, it is not only a matter of civil case but also criminal case. Therefore, the companies may be subjected to both civil and criminal liability.